From Self-Legislation to Self-Determination: Democracy and the New Circumstances of Global Politics. Issue 1 (February 2016) - Bohman, James
Abstract : It is a distinctive feature of the global political order that democracy is no longer confined to nation-states, characterized by extensive and overlapping constituencies. It is important to think of the significance of these developments for individuals' self-determination, which may be undermined in different ways. Here it is argued that democracy must serve to delegate power to complex units of decision making which favour self-determination. Contestability is part of this form of self-determination, allowing forms of politics to emerge based on the democratic rights and powers of self-determining, non-dominated citizens.